Development of regionalized SPFs for two-lane rural roads in Pennsylvania. (November 2017) - Li, Lingyu; Gayah, Vikash V.; Donnell, Eric T.
Highlights: Methodology presented to estimate regional SPFs within a state. SPFs estimated at state, district and county levels (including local adjustment factors). Regional SPFs appropriate for states with large regional differences in safety performance. Abstract: The American Association of State Highway and Transportation Officials' Highway Safety Manual (HSM) contains safety performance functions (SPFs) to predict annual crash frequencies for several roadway types. When applying these SPFs in a jurisdiction whose data were not used to develop the SPF, a calibration factor can be applied to adjust the expected crash frequency estimate to statewide or local conditions. Alternatively, the HSM suggests that transportation agencies may develop their own SPFs in lieu of applying the calibration factor to the HSM SPFs. However, the HSM does not provide guidance on the appropriate level of regionalization that should be adopted for either method, even though safety performance may vary considerably within a state. In light of this, the present study considers the development of local or regionalized SPFs for two-lane rural highways within the Commonwealth of Pennsylvania. Three regionalization levels were considered: statewide, engineering district and individual counties. The expected crash frequency for each level of regionalization was compared to the reported crash frequency over an eight-year analysis period. The results indicate that district-level SPFs with county-level adjustment factors provide better predictive accuracy than the development of a statewide SPF or application of the HSM-calibrated SPF. The findings suggest that there are significant differences in safety performance across engineering districts within Pennsylvania. As such, other state transportation agencies developing SPFs or using calibration factors may also consider how variations across jurisdictions will affect predicted crash frequencies.